Geschlechterdifferenz in der politischen Debatte zur europäischen Union? - Schunter-Kleemann, Susanne (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1993)
Recent referenda and surveys in Denmark, Sweden, Switzerland and Austria show that women are the most determined opponents against the project of an Europoean Political Union. This article deals with the political debate among women in some European countries and identifies the main topics which stand in the center of women's reservations against the Maastricht Treaty. The new EC Information Policy (Le Clercq Report 1993) is presented, which claims to win back the confidence of the European Citizens. This new communication strategy adresses to women in a special way,